Jazz pedagogical strategies: an A/R/Tographic investigation into the implementation of the South African jazz CAPS syllabus - Rungan, Natalie (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
The Jazz stream of the Curriculum and Assessment Policy Statement Further Education and Training music curriculum was introduced in South Africa in 2012 (DBE, 2011a). Despite the intentions of the government to promote diversity, social transformation, and inclusion, subject music is still weighted towards Western Art Music, perpetuating past biases of a Eurocentric model for music education. This study, which uses a mixed-method approach, seeks to create strategies to advance Jazz education in South Africa through an a/r/tographic analysis of the author's Jazz pedagogical methods at Durban High School in KwaZulu Natal, South Africa. Key approaches include curriculum theory, currere, a/r/tography, among others. After reviewing Jazz pedagogy in the U.S.A. and South Africa as a starting point, using Pinar's (1994) method of currere, the author demonstrates how past personal music educational processes have led to present Jazz pedagogical methods. Six original compositions were written that outline the influences that infused these methods and added to the creative output related to this research. Interviews were conducted with key stakeholders in the Jazz community to gain perspective about the current state of Jazz education, and with students to provide insight into their reactions to the Jazz stream of CAPS. This presents new information about the curriculum from a learners' perspective. Ethical clearance for research with children was sought and received (Appendix A). Findings show that the ability of learners to recognise the value in, and identity relating to, their African culture through Jazz points to a pivotal departure from previous Eurocentric music education models. However, despite South Africa being positioned as one of the only countries offering Jazz as a subject choice to high school learners, the selection of Jazz in the subject of Music remains underutilised. This study concludes that for Jazz education to advance in South African high schools, there needs to be intentional engagement with Jazz professionals at the high school level.
Keywords: Jazz Instruction and study; Durban High School Curricula; Jazz Outlines, syllabi, etc.; Curriculum-based assessment -- South Africa; Jazz vocals; Jazz education; South Africa. Department of Basic Education